2011
DOI: 10.1002/cjoc.201190127
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hydrocortisone in Cosmetics by CdSe/CdS Quantum Dots‐Based Fluoroimmunoassay Using Magnetic Fe3O4/Au Nanoparticles as Solid Carriers

Abstract: This work demonstrated the feasibility of detecting hydrocortisone in cosmetics using a novel CdSe/CdS quantum dots-based competitive fluoroimmunoassay with magnetic core/shell Fe 3 O 4 /Au nanoparticles (MCFN) as solid carriers. Hydrocortisone antigen was labeled with the synthesized core/shell CdSe/CdS quantum dots (QDs) to form the antigen-QDs conjugate. Meanwhile, hydrocortisone antibody was incubated with MCFN and the immobilized antibody was obtained. The immobilized antibody was then mixed sequentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…11(B)). 158 A spread of a 10-L drop of a mixture of 10 5 cfu/mL bacteria and 3 g/mL Fe 3 O 4 @Au NPs on a silicon surface can be effectively condensed into a highly compact dot within 5 min by applying an external point magnetic field, resulting in 60 times more concentrated bacteria in the dot area than on the spread area 159 demonstrated the feasibility of detecting hydrocortisone in cosmetics using a novel CdSe@CdS quantum dot-based competitive fluoroimmunoassay with magnetic core-shell Fe 3 O 4 @Au NPs as solid carriers. The analyte concentration was quantified by measuring the fluorescence intensity of the unbound hydrocortisone antigen-QDs conjugates.…”
Section: Dna-based Biosensorsmentioning
confidence: 99%
“…11(B)). 158 A spread of a 10-L drop of a mixture of 10 5 cfu/mL bacteria and 3 g/mL Fe 3 O 4 @Au NPs on a silicon surface can be effectively condensed into a highly compact dot within 5 min by applying an external point magnetic field, resulting in 60 times more concentrated bacteria in the dot area than on the spread area 159 demonstrated the feasibility of detecting hydrocortisone in cosmetics using a novel CdSe@CdS quantum dot-based competitive fluoroimmunoassay with magnetic core-shell Fe 3 O 4 @Au NPs as solid carriers. The analyte concentration was quantified by measuring the fluorescence intensity of the unbound hydrocortisone antigen-QDs conjugates.…”
Section: Dna-based Biosensorsmentioning
confidence: 99%
“…Conventional liquid-liquid and solid-liquid extraction-based procedures are common strategies for sample preparation in both official and published methods. [7][8][9][10][11][12][13][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Nevertheless, they present some disadvantages. Generally, extraction procedures involve the use of high volumes (5 to 60 mL) of toxic organic solvents such as tetrachloromethane, chloroform, dichloromethane diethyl ether, methanol, etc.…”
Section: Classical Extraction In Cosmetic Analysismentioning
confidence: 99%
“…34 In many cases, additional stages such as shaking, heating, centrifugation and ltration are necessary resulting in laborintensive and time-consuming procedures. [17][18][19][20][21][22] For example, have recently developed an extraction method for the determination of hydrocortisone in cosmetics: 50 g of sample is stirred with 200 mL of methanol until homogeneous dispersion of the sample; aer centrifugation and ltration, the solvent is evaporated; the residue is solubilized in 100 mL of ethylacetate, stirred for 1 h, ltered, dried again and re-solubilized in 1 mL methanol. 21 This long procedure, which limits sample throughput, is necessary in order to improve sample clean up.…”
Section: Classical Extraction In Cosmetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The ELISA methods have proven to be a rapider and lower-cost screening tool for compound residues with lower detection limits and easier pretreatment in comparing with instrumental methods (Luo et al, 2015;Song et al, 2019). Until now, the research about the development for immunoassays method for HYD by fluoro-immunoassay (Wang, Wei, Tao, & Dai, 2011), enzyme-linked immunosorbent assay and immunochromatographic assay (Wang, Xie, et al, 2017) has been reported. However, most of the reported assays were developed for food samples.…”
Section: Introductionmentioning
confidence: 99%